Serum miR-142-3p is associated with early relapse in operable lung adenocarcinoma patients - Kaduthanam, Sajo; Gade, Stephan; Meister, Michael; Brase, Jan Christoph; Johannes, Marc; Dienemann, Hendrik; Warth, Arne; Schnabel, Philipp Albert; Herth, Felix; Sültmann, Holger; Muley, Thomas; Kuner, Ruprecht (Lung cancer, 2013)
The outcome of resectable non-small cell lung cancer (NSCLC) is critically determined by metastatic spread: About 30-50% of early-stage NSCLC patients encounter tumour recurrence within 5 years after surgery. A biomarker-driven stratification of early-stage lung cancer with a high risk of recurrence may improve therapy management and patient care. The aim of this study was to identify microRNAs (miRNAs) in serum of patients associated with early relapse in pulmonary adenocarcinoma. Serum samples were collected from 204 patients before surgery. miRNA screening was done using qRT-PCR based low-density arrays (664 miRNAs) comparing adenocarcinoma patients (n=40) with and without recurrence 24 months after surgery. Selected miRNAs associated with disease recurrence were validated in an independent patient cohort (n=114). miRNAs were also measured in advanced adenocarcinoma patients (n=29), and individuals with benign pulmonary diagnosis (n=21). Circulating miR-142-3p (p=0.005) and miR-29b (p=0.01) were identified in the screening and confirmed in the validation cohort to be increased in sera of early-stage adenocarcinoma patients suffering from recurrence within 24 months. Elevated miRNA levels were exclusively observed in the group of high-risk patient diagnosed for operable adenocarcinoma compared with benign diagnosis or advanced tumour disease. The differentiation between pulmonary adenocarcinoma patients with low and high risk for recurrence was improved by accounting for both miR-142-3p levels and tumour stage (p=0.007; AUC=0.78). In conclusion, circulating miR-142-3p was found to be associated with a high risk of recurrence in early-stage lung adenocarcinoma patients, and a putative serum marker for risk assessment.
Gesehen am 13.04.2021